Humanitarian spill-over: the expansion of hybrid humanitarian governance from camps to refugee hosting societies in East Africa. - Jansen, Bram J.; de Bruijne, Milou (Journal of Eastern African Studies, 2020)
The impact and effects of protracted refugee camps on their host environments in East Africa has been the subject of much academic attention since the late 1990s. Such camps are often viewed as exclusionary spaces that isolate refugees from their host societies. Recent analyses, however, posit such camps as hybrid spaces, with fluid boundaries, that provide socio-economic opportunities and are potential drivers of development. Less thinking has gone into how forms of (humanitarian) governance emanate from such camps and impact their host environments. This paper is based on ethnographic research in and around refugee camps in Kenya and Tanzania. Grounded in a spatial analysis of camp development processes, this paper explores the notion of 'humanitarian spill-over'. It argues that camps' specific governmental processes and bureaucratic power come to co-govern and co-shape socio-spatial relations beyond the boundaries of the camp and the initial targets of humanitarian concern. By analysing the socio-spatial effects of long-term humanitarian governance, this paper contributes to, debates about camps as hybrid spaces and locates experiments with developmental approaches to camp environments in East Africa in a history of a more organic process of spill-over. We show how the spill-over is increasingly posited as intention rather than effect.